Dizziness as a first alarming symptom to neurological hospital admission: reasons and differentiation problem - a pilot study. - Mielańczuk-Lubecka, Beata; Krzysztoń, Karolina; Zdrowowicz, Agata; Stolarski, Jakub; Piaścik, Rafał; Domitrz, Izabela (Journal of Medical Science, 2021)
Aim. This prospective study aimed to assess the diversity of diagnoses in patients hospitalized in the neurology department, in whom the occurrence of dizziness was the presenting complaint during qualification for hospitalization, based on a joint assessment performed by a doctor and a physiotherapist and the implementation of treatment, including physiotherapy.Material and Methods. The study included consecutive patients selected from 2155 individuals hospitalized between 2018 and 2020 in the Neurology Unit who reported dizziness as the presenting complaint.Results. 100 patients (the mean age 58.68±16.57) were qualified for the study: 53 men (the mean age 59.47±15.44) and 47 women (the mean age 57.79±17.88). In the overwhelming number of cases, dizziness was associated with a vascular incident. However, cases of vertigo were also reported.Conclusion. A variety of diagnoses were made in patients hospitalized in the neurological department in whom the occurrence of dizziness was the presenting complaint during qualification for hospitalization.
Keywords: stroke; vertigo; dizziness assessment; acute dizziness; emergency neurology